Age increase and weight reduction effects on bone mineral density and content - Slavica Subeska-Stratrova; Dejan Spasovski (My University, 2019)
Dual energy x-ray absorptiometry (DXA) scan is considered to be the gold standard for diagnosing and monitoring bone loss and evaluating the degree of osteoporosis. The DXA scan calculates bone density based on the amount of radiation absorbed by the bone, and compares patient’s bone strength and bone density to that of young adults with normal bone density and to other persons of the same age. DXA evaluates total body bone mineral density (BMD) expressed in grams (gr) and bone mineral content (BMC) expressed in gr/cm2 , as well as regional BMD and BMC values for the arms, legs, hips, head and trunk (which includes ribs, pelvis, thoracic spine, and lumbar spine). BMD is typically expressed in T-scores. Normal BMD T-score is greater than -1, and in osteoporosis BMD is characterized with T-score below -2.5. This study evaluated lumbar spine and hip bone lost for a period of 12 years, where in the last three years there was a reduction of the total body mass for mean 14 kg and evaluation was performed on total and regional BMC and BMD values. Mean value L1-L4 vertebra BMD 1.13±0.06 kg/m2 reduced to 1.05±0.04 kg/m2 (p<0.001) and mean value L1-L4 vertebra BMC 55.12±5.89 gr reduced to 54.25±6.2 gr (p<0.001) for 12 years period. Last 3 years change of spine BMD was associated with reduction of the mean L4 lumbal vertebra T-score from -0.7 to -1.7 indicating developed osteopenia on this vertebra. Also the highest reduction of BMC of mean 22.08% was detected on L4. Neck mean BMD basal value was 0.88±0.08 kg/m2 and reduced significantly for 12 years to 0.74±0.07 kg/m2 (p<0.001). Trochanter mean BMD basal value was 0.71±0.08 kg/m2 and reduced significantly in 12 years to 0.64±0.03 kg/m2 (p<0.02). Total hip mean BMD basal value was 0.89±0.08 kg/m2 and reduced to 0.74±0.09 kg/m2 (p<0.001). Total hip mean BMC 25.34±4.62 gr reduced to 22.16±2.92 gr (p<0.46). Total hip mean BMD lowered for mean value of 13.71%, BMC lowered for 13.61% and % of BMD reduction was 13.48%. The last three years regional BMD values were with T-score in normal range and reduced to osteopenic levels with significance of p<0.014 for arms BMD change, p<0.01 for trunk, p<0.033 for pelvis, p<0.027 for ribs, and p<0.05 for total BMD change. Legs BMD values stayed in normal range. It can be concluded that age, as well as the weight reduction influenced negatively on hip, spine and regional BMD and lowered it significantly from the normal values to osteopenic values, indicating the need of bone BMC and BMD reduction prevention. Bone densitometry is a very safe, painless and quick test that can measure bone strength and predict fracture risk before the patient develops osteoporosis and hence effective preventive therapy can be started. Bone density tests are also used to monitor the response to particular medications. Our experiences in body composition and osteoporosis DXA assessment were evaluated in this study
Keywords: Dual energy x-ray absorptiometry; body composition; bone mineral density; bone mineral content